A Full Brain 3D-Magnetic Resonance Spectroscopic Imaging Study of Migraine and Post-Traumatic Headache - Simona Nikolova; Todd J. Schwedt; Yuxiang Zhou; Brian W. Chong; Gina Dumkrieger; Catherine D. Chong (Neurotrauma Reports)
Magnetic resonance spectroscopic imaging provides a means to quantify brain metabolites including N-Acetylaspartate (NAA), choline (Cho), creatine (Cr), myoinositol (Ins), and glutamate and glutamine (Glx). The goal of this work was to investigate the metabolite differences between participants with migraine, participants with acute post-traumatic headache (PTH) with migraine-like phenotype, and healthy controls. For spectroscopy acquisitions, a 3D echo-planar spectroscopic imaging sequence was used with full brain coverage. 3D metabolite maps for NAA, Cho, Cr, Ins, and Glx were compared between participants with migraine (n = 12), participants with acute PTH (n = 10), and healthy controls (n = 11) using a full factorial design with significance defined as p < 0.05 with family-wise error corrections for multiple comparisons. The migraine group showed increased Cho and Ins in the right hippocampus and increased Ins in the bilateral parahippocampal regions, left inferior temporal, and bilateral fusiform areas relative to healthy controls. Relative to healthy controls, the acute PTH cohort had decreased NAA in the right precuneus, increased Glx in the right lingual and the right calcarine gyrus, and increased Ins in the left amygdala. Relative to individuals with migraine, those with acute PTH had higher Glx in the right calcarine gyrus, decreased Glx in the left insula, decreased Ins in the left fusiform gyrus, and increased NAA in the left frontal inferior area. The metabolite differences between migraine, PTH, and healthy controls observed in this study could provide insights into the mechanisms and consequences of migraine and PTH.